Analisis Kebutuhan Media Dan Bahan Ajar Berbasis Augmented Reality Dalam Pembelajaran Ipa Pendekatan STEAM Keterampilan Abad 21 Guru Sekolah Dasar - Rahmawati, Nanik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Augmented reality or berimbuh reality, is a technology that combines two-dimensional and / or three-dimensional virtual objects into a real three-dimensional environment and then projects these virtual objects in real time. The use of AR can increase the activities of students to blend into a real learning environment no longer abstract. The combination of virtual and real objects brings interaction anytime and anywhere, which is capable of presenting 3D objects which are the most important features of AR, resulting in a learning experience that is different from before. The main purpose of this research is to focus on the teacher's views regarding the need for media, teaching materials and to explore the factors that become obstacles in the acceptance of AR, especially in science learning in elementary schools. This study took a sample of elementary school teachers in Purwantoro district, Wonogiri regency with a total population of 35 teachers with a sample of 18 teachers. The sample includes teachers with years of experience in teaching with different schools in Purwantoro sub-district, Wonogiri district. The result is that AR in STEAM learning has not been maximally applied in schools; There is a need for more in-depth socialization and training, the need for media and science teaching materials based on AR in STEAM learning in 21st century skills in primary schools still needs to be developed.